2011
DOI: 10.4081/rr.2011.e15
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women living with fibromyalgia: an exploratory study of their information needs and preferences

Abstract: Women living with fibromyalgia consistently report experiencing a change in their lives in terms of stigma, inability to work, isolation from society and difficulty in managing their illness. Lack of understanding and knowledge about their disease has been linked to compromised health and quality of life. The aim of this study was to explore the experiences of information use of women living with fibromyalgia. A descriptive phenomenology was used for this study. Participants were identified through gatekeepers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In a study of information-seeking experiences of patients with fibromyalgia, we found that patients experienced a similar frustration with health care providers not being able to provide accurate and useful information about their health problem [39, 40]. Patients did express concerns for quality information similar to that reported in a previous qualitative study of neck and back pain [23].…”
Section: Discussionmentioning
confidence: 60%
“…In a study of information-seeking experiences of patients with fibromyalgia, we found that patients experienced a similar frustration with health care providers not being able to provide accurate and useful information about their health problem [39, 40]. Patients did express concerns for quality information similar to that reported in a previous qualitative study of neck and back pain [23].…”
Section: Discussionmentioning
confidence: 60%
“…Not only is interdisciplinarity the recommended approach for chronic pain, but this study suggests that it is something patients are explicitly or implicitly seeking. Participants in this study echoed a need for information about FM, 29 highlighting how few participants had received biopsychosocially framed approaches like pain education, energy conservation tools, and psychosocial interventions. A further outcome of this study emphasizes how participants employed strategies like personal research, self-advocacy, and self-management to compensate for these gaps in care.…”
Section: Discussionmentioning
confidence: 92%
“…The third most preferred choice of JP delivery was at the clinic. Our previous studies of information access preferences in patients with fibromyalgia 21 22 indicated that face-to-face interaction with healthcare providers was the most preferred way of getting information and it is likely that this is the positive aspect for attending a clinical site. Previous review has indicated that patient-centred interaction styles related to the provision of emotional support and allowing patient involvement in the consultation process may enhance the therapeutic alliance between clinician and patient.…”
Section: Discussionmentioning
confidence: 99%